2017
DOI: 10.18632/oncotarget.23015
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory activity of gallic acid against DNA methylation: application of gallic acid on epigenetic therapy of human cancers

Abstract: Epigenome aberrations have been observed in tobacco-associated human malignancies. (−)-epigallocatechin-3-gallate (EGCG) has been proven to modulate gene expression by targeting DNA methyltransferases (DNMTs) through a proposed mechanism involving the gallate moiety of EGCG. We show that gallic acid (GA) changes the methylome of lung cancer and pre-malignant oral cell lines and markedly reduces both nuclear and cytoplasmic DNMT1 and DNMT3B within 1 week. GA exhibits stronger cytotoxicity against the lung cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…In addition, epigenome-protecting abilities of GA were also observed in tobacco-associated cancers. GA reduced nuclear and cytoplasmatic DNA methyltransferases in H1299 cells [37]. GA was also found to be a potent inhibitor of HDAC8 and class IIa/b HDAC activity [38].In addition, GA demonstrated anti-invasive effects in human nasopharyngeal carcinoma cells NPC-BM1 through the inhibition of p38 MAPK signaling pathway, this was due to suppressed transcription of MMP-1 by down-regulation of Ets1 and c-Jun, c-fos of the AP-1 [39].…”
Section: Gallic Acidmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, epigenome-protecting abilities of GA were also observed in tobacco-associated cancers. GA reduced nuclear and cytoplasmatic DNA methyltransferases in H1299 cells [37]. GA was also found to be a potent inhibitor of HDAC8 and class IIa/b HDAC activity [38].In addition, GA demonstrated anti-invasive effects in human nasopharyngeal carcinoma cells NPC-BM1 through the inhibition of p38 MAPK signaling pathway, this was due to suppressed transcription of MMP-1 by down-regulation of Ets1 and c-Jun, c-fos of the AP-1 [39].…”
Section: Gallic Acidmentioning
confidence: 91%
“…In therapeutics a post-fermentation oolong tea extract (PFOTE) GA-enriched using Aspergillus sojae was associated with further enhanced demethylation abilities. PFOTE also increased sensitivity to cisplatin and showed stronger antiproliferative abilities when compared with oolong tea extract [37]. Furthermore, an ability of GA to potentiate side effects of conventional chemotherapeutic drugs was evaluated in HeLa cervical cancer cells.…”
Section: Gallic Acidmentioning
confidence: 99%
“…GA is a primary anti-oxidant component of tea extract. Ayurvedic herbs have large quantities of GA [26,30,31]. Experimentally, GA has been documented to produce anti-hyperlipidemic, cardioprotective, anti-diabetic activity [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…However, at much lower concentrations, the drug can play its role in the treatment process in cancer cells. Many studies have shown that GA is a powerful antioxidant compound in the death of cancer cells (43,44). Based on the results in Figure 2 and Table 1, GA interacts with amino acids in binding site by ten hydrogen bonds and six hydrophobic bonds.…”
Section: Discussionmentioning
confidence: 96%